The Mediating Effect of Innovation in the Relationship Between Social Capital and Halal Culinary Business's Competitive Advantage - Salihah Khairawati; Nur Wening; Tulus Haryon0; Wijiharta Wijiharta; Irton Irton (Cita Konsultindo Research Center, 2023)
This study aims to examine how the role of innovation in its influence between social capital and competitive advantage. Research conducted on 150 halal culinary businesses in Yogyakarta province, Indonesia. This research uses purposive sampling techniques, primary data are collected through questionnaires distributed to managers and owners of halal culinary businesses. Data is processed using Smart PLS 3.0 software. The results prove the social capital has a direct effect on competitive advantage. Social capital has a positive and significant effect on innovation. Innovation has a positive and significant effect on competitive advantage. The results of the mediation role test obtained that social capital has a positive and significant effect on competitive advantage through innovation variables. That is, innovation in this research model is a mediating variable. This research clarifies the importance of social capital and innovation in achieving competitive advantage.